STUDI HARMONIK PADA SUMBER LISTRIK AKIBAT PENGGUNAAN LAMPU LED, LHE, DAN TL - Pahiyanti, Novi Gusti; Soewono, Soetjipto (ENERGI & KELISTRIKAN, 2015)
Along with the development in the field of lighting, LED, LHE and TL is now widely used as a good lighting for home lighting and street lighting. The lamp is also said to be capable of energy saving lamps produce light more efficiently than incandescent bulbs. Energy saving lamp is a nonlinear load that can cause disturbances in electrical power systems are referred to as harmonics. As an energy-saving lamp has a non-linear load that produces both harmonic current harmonic distortion and voltage harmonics. In this research, a combination of LED lights, LHE, and TL. Of the three lights which have the greatest harmonics are LED lights. To suppress harmonics of LED lights can be done with a combination of LED lights and lights LHE.